Exploring the outcomes of digital marketing on historic sites' visitor behaviour - Amorim, L. A. de.; Sousa, B. B.; Dias, Á. L.; Santos, V. R. (Journal of Cultural Heritage Management and Sustainable Development, 2024)
Purpose – Digital communication and social media have an increasing importance in society and in tourism boosting. This study aims to analyse the role of digital marketing in the destination image and visitor loyalty of historic sites. Design/methodology/approach – Using a mixed-method approach combining survey data from 318 respondents and three in-depth interviews. Using structural equations modelling results reveals experience, satisfaction, image and loyalty are concepts to be considered by the destinations’ digital marketing promotion, as well as the increasing use of digital marketing by tourists, in the sense that tourists are increasing the habit of checking the opinion of others before scheduling their trip and gives them more importance, and a growing importance is given by tourists to the web/social networks of places they intend to visit. Findings – This study contributes to the theory on tourism digital marketing which can be transposed to organizations management in order to encourage discussion on the processes of capture, retention and loyalty of target audiences. Research limitations/implications – To enhance the importance of digital marketing in the process of the tourist development of the city, it is fundamental to define a clear strategy for attracting and responding to the greatest demand from cultural tourists who are increasingly interested in actively participating in learning experiences. Practical implications – The results show that digital communication and social media have an increasing importance in society and in tourism boosting and economy recovery. Social implications – The paper presents digital marketing as a possible factor in tourism development and social inclusion, advancing practical measures aimed at social justice through a fairer distribution of tourism revenues and the defence of historic centre residents’ way (i.e. Barcelos’), and quality of life. Originality/value – The authors suggest the development of a strategic digital marketing plan applied to the development and promotion of tourism in the city of Barcelos (Portugal), to complement the research presented here, thus contributing with a more practical perspective of the subject under study.